Unsaturated soil mechanics in engineering practice - Fredlund, D. G. (Delwyn G.), 1940 (John Wiley & Sons, 2012)
"Here is the definitive guide to unsaturated soil by the world's expert in the area of unsaturated soil mechanics. This volume features the latest information and replaces the leading text in the field, also written by this author team. The text offers state-of-the-art information to deal with the practical engineering problems resulting from unsaturated soil. Greater emphasis has been placed on the using the soil-water characteristic curve in solving practical engineering problems, as well as the quantification of thermal and moisture boundary conditions based on weather data"